Sedekah Botol Plastik di Mushola Sebagai Model: Strategi Memakmurkan Mushola dan Menjawab Krisis Lingkungan - Faozan, Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study explores the contribution of the administrators and congregation of the Baitul Hikmah Mosque, Sokopuro, Diwek, Jombang in implementing plastic bottle alms and echoing piety for sustainable living through. A qualitative phenomenological approach was used with in-depth interview techniques, observation, and document analysis. The Plastic Bottle Waste Alms Program has a positive impact on congregation awareness andreducing environmental footprint. The results show that the administrators and congregation of the Mosque have succeeded in integrating Islamic values in sustainable practices by utilizing the mosque as an environmental education center. The collaborative program with the Tebuireng Waste Bank and the Baitul Hikmah Mosque has supported the successful implementation of the plastic bottle alms program. This study concludes that the program can be a strategic model for other mosques to increase public awareness and participation in environmental conservation. Thus, it also makes the place of worship as one of the religious movements as a center for social change based on Islamic teachings in responding to the environmental crisis.